MORE THAN ONE WAY TO PRODUCE PROTEIN DIVERSITY: DUPLICATION AND LIMITED ALTERNATIVE SPLICING OF AN ADHESION MOLECULE GENE IN BASAL ARTHROPODS. (4th July 2013) - Brites, Daniela; Brena, Carlo; Ebert, Dieter; Du Pasquier, Louis
<x xml:space="preserve">Abstract</x> Exon duplication and alternative splicing evolved multiple times in metazoa and are of overall importance in shaping genomes and allowing organisms to produce many fold more proteins than there are genes in the genome. No other example is as striking as the one of the Down syndrome cell adhesion molecule (Dscam) of insects and crustaceans (pancrustaceans) involved in the nervous system differentiation and in the immune system. To elucidate the evolutionary history of this extraordinary gene, we investigated Dscam homologs in two basal arthropods, the myriapod Strigamia maritima and the chelicerate Ixodes scapularis. In both, Dscam diversified extensively by whole gene duplications resulting in multigene expansions. Within some of the S. maritima genes, exons coding for one of the immunoglobulin domains (Ig7) duplicated and are mutually exclusively alternatively spliced. Our results suggest that Dscam diversification was selected independently in chelicerates, myriapods, and pancrustaceans and that the usage of Dscam diversity by immune cells evolved for the first time in basal arthropods. We propose an evolutionary scenario for the appearance of the highly variable Dscam gene of pancrustaceans, adding to the understanding of how alternative splicing, exon, and gene duplication contribute to create molecular diversity associated with potentially new cellular functions.